2020
DOI: 10.3389/fncel.2020.00190
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Immune Cell Infiltration to the Multitasking Microglia Response and TNF Receptor 2 Induction in the Multiple Sclerosis Brain

Abstract: Veroni et al. Microglia Activation in Multiple Sclerosis of cytotoxic adaptive immunity in driving detrimental microglia activation and the concomitant healing response. It also shows that TNFR2 is an early marker of microglia activation and promotes myelin synthesis, suggesting that microglial TNFR2 activation can be exploited therapeutically to stimulate CNS repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 104 publications
(186 reference statements)
1
9
0
Order By: Relevance
“…IFNγ and TNFα have been shown to induce RBP mislocalization in cell lines [27,40]. In MS tissues, there is elevated expression of IFNγ and TNFα and their receptors in immune cell infiltrates, neurons, and oligodendrocytes in grey and white matter [44,47]. These data suggest that the presence of pro-inflammatory cytokines within these areas and the cells themselves may contribute to RBP dysfunction and, consequently, neuronal damage.…”
Section: Discussionmentioning
confidence: 92%
“…IFNγ and TNFα have been shown to induce RBP mislocalization in cell lines [27,40]. In MS tissues, there is elevated expression of IFNγ and TNFα and their receptors in immune cell infiltrates, neurons, and oligodendrocytes in grey and white matter [44,47]. These data suggest that the presence of pro-inflammatory cytokines within these areas and the cells themselves may contribute to RBP dysfunction and, consequently, neuronal damage.…”
Section: Discussionmentioning
confidence: 92%
“…More recently, Veroni and colleagues (2020) found a significant upregulation of TNFR1 in subpial GM lesions and in both active and normal appearing white matter lesions. Interestingly, the authors found an even more increased expression of TNFR2 mRNA in white matter lesions, including chronic active lesions, without changes in the GM and in normal white matter areas surrounding the rim of active lesions, suggesting reparative mechanisms in the areas close to damaged zones [ 154 ].…”
Section: Evidence For Tnf Involvement In Pathological Hallmarks Ofmentioning
confidence: 99%
“…Increasing evidence from in vitro and in vivo studies points to a crucial role of TNF signalling in mediating both WM and GM pathology. 25 28 CSF TNF levels in progressive MS patients have been linked to altered synaptic transmission, with exacerbation of glutamatergic transmission and neuronal damage when incubating CSF with corticostriatal slices. 29 , 30 Recently, persistent expression of CSF TNF along with IFN gamma has been described as a potent inducer of meningeal inflammation and subpial demyelination in the myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE) model.…”
Section: Discussionmentioning
confidence: 99%